Determining Research Priorities Through Partnership with Patients: An Overview. Issue 2 (30th November 2014) - Barnieh, Lianne; Jun, Min; Laupacis, Andreas; Manns, Braden; Hemmelgarn, Brenda
Abstract There is an increasing level of emphasis being placed on health care providers and funders to incorporate patient‐centered care into research. Involving patients and caregivers in establishing research priorities ensures the relevance of the research produced. Priority setting is a process that can be used to produce a robust set of research questions that researchers can address over the coming years. One of the methods for determining research priorities that involves patients, caregivers and clinicians is the James Lind Alliance priority setting partnership model. This method is focused on being exclusive, transparent, and evidence‐based. Using a recent example of patients on or nearing dialysis, we highlight the key steps to assess research priorities in patients, caregivers and clinicians: (i) formation of a steering committee to guide the overall process; (ii) form priority setting partnerships; (iii) identify and gather research uncertainties; (iv) process and collate submitted research uncertainties; and (v) final priority setting workshop to determine the top 10 research priorities.